Functional safety research of battery management system based on risk graph methods. Issue 1 (January 2021) - Chen, Mingsheng; Xie, Guiting; Ming, Zhimao; Liu, Guixiong; Li, Wei
Abstract: In order to clarify the functional safety integrity hierarchy of the battery management system, this paper uses risk map analysis to qualify the battery management system failure event of an alarm device. The relationship among six risk parameters and four levels of safety integrity are built through specific risk. Thirteen contents are detailed and in according to four risk parameters. The results show that the functional safety outcomes of the battery management system can be classified into seven categories, and safety integrity was determined to be level I using the ten mapped paths in the risk map.